Fermentação em estado sólido assistida por ultrassom para a produção de enzimas de degradação de parede celular - Mezadri, Ethiane Teixeira (2019)
The agro-industry waste is low cost, high availability and it can be transformed into products of important economic value. The biotransformation of these substrates into compounds with an aggregated value from the solid-state fermentation by the cultivation with filamentous fungi has been highlighted and presents significant results. The application of the ultrasound bath is a current technology that can produce a positive effect on the enzymatic activity. However, the number of works using it during the fermentation process to increase the enzymatic activity before the extraction is still very limited. In this way, the work seeks to evaluate the production of enzymes associated with cell wall degrading (chitinase, β-1,3-glucanase and cellulases – exocellulase, and endocellulase) from different agro-industrial substrates using the microorganism Trichoderma harzianum by means of solid-state fermentation. Preliminary tests were made with this microorganism in different substrates to enable the choice of the best way and the evaluation of the great conditions for the production of the enzymes. After statistical analysis and choice of Rice type 1 as the best substrate, a central composite design (CCD) was performed considering a factorial design 24 with 3 central points to evaluate the influence of temperature, humidity, solution concentration of nutrient, and concentration of yeast extract in the enzymatic activity. The highest activity of 31,3 U/g, 60,4 U/g, 40,3 U/g e 23,8 U/g for chitinases, exocelullase, endocellulase, and β-1,3-glucanases respectively was obtained after 240 hours (10 days), and it was observed that the humidity presented significance and negative effect in all tests. In a second step, the moisture content of the medium and the immersion time of the fermentation in the ultrasound bath were evaluated to verify the influence on the enzymatic activity. The results of the enzymatic activity were analyzed statistically by ANOVA and Tukey’s Test. It was possible to observe that for all enzymes that were analyzed, the ultrasound effect was positive. After 240 hours (10 days) of fermentation using 4 hours of ultrasound per day during the fermentation was obtained through the analysis of the extracts an increase of 261% in the activity of chitinases, 122% in the activity of exocellulases, 84% of endocellulases, and 311% in the activity of β-1,3-glucanases when compared to the extracts obtained from the tests performed after the same period of time in the fermentation without the use of ultrasound.